Проблеми енергозабезпечення і шляхи їх вирішення в автономній Республіці Крим - Babenko G.A.; Kibovsky S.A. (General Energy Institute of the National Academy of Sciences of Ukraine, 2002)
A state of resource and energy supply of the Crimea republic is considered. The main directions of decline of energy resources consumption in case of introduction of organizational and not expenditure energy-saving measures, technologies, equipment are definite, and also in case of untraditional and renewed energy sources using.